Effects of Dietary Preference on the Experience of Anxiety, Depression and Acute Stress Response - (:unkn) unknown (My University, 2014)
Research has demonstrated that high saturated fat and low carbohydrate consumption may provide physiological benefit in the treatment of major neurological disorders, though not much research has explored if these benefits extend to the experience of anxiety, depression, stress and physical symptoms. The purpose of this study was to explore the relationship between fat consumption and negative emotional/physiological states (anxiety, depression, stress and physical symptoms). This study also explored how fat consumption can alter one's response to an acute stress. Participants completed an online survey indicating their food preferences and their responses to a number of self-report scales such as the Physical Symptoms Inventory (PSI), Perceived Stress Scale (PSS), Hospital Anxiety and Depression Scale (HADS) and Depression, Anxiety and Stress Scale (DASS21). From those that completed the online survey, participants were recruited to complete the lab portion of the study. Participants initially completed the Positive and Negative Affective Schedule (PANAS) and Brief Fear of Negative Evaluation (BFNE), they then completed the Montreal Imaging Stress Task and completed a follow up PANAS. Heart rate (HR), cardiac output (CO), stroke volume (SV) and skin conductance level (SCL) were recorded throughout the study. Following the study, high frequency heart rate variability (HF) and percentage of normal to normal beats greater than 50 msec (pNN50) was calculated and participants were split into three groups based on saturated/mono-saturated fat consumption. It was found that participants who consumed high amounts of saturated/mono-saturated fat demonstrated high HF and pNN50 values prior to the MIST, increased flexibility in response to the MIST and a return to baseline following the MIST. Increased fat consumption was also associated with lower depression scores (HADS) and lower baseline negative affect (PANAS). There was no significant change in HF or pNN50 for those who consumed a moderate amount of saturated/mono-saturated fat. For those participants who consumed a low amount of saturated/mono-saturated fat, there was a decrease in pNN50 during the MIST. Results indicate that increased fat consumption may have generated a more flexible and favorable autonomic state, while those who consumed low amounts of fat demonstrated a decrease in HRV during the MIST and minimal recovery back to baseline following the MIST.
Keywords: Anxiety; Cardiovascular; Diet; Physiology; Saturated Fat; Stress